1996
DOI: 10.1161/01.cir.93.5.866
|View full text |Cite
|
Sign up to set email alerts
|

Increased Activation of Sympathetic Nervous System and Endothelin by Mental Stress in Normotensive Offspring of Hypertensive Parents

Abstract: The activity of the sympathetic nervous system and plasma norepinephrine and endothelin levels are increased during mental stress only in offspring of hypertensive parents, whereas the response to hypoxia was similar in offspring of hypertensive and normotensive parents, suggesting a genetically determined abnormal regulation of the sympathetic nervous system to certain stressful stimuli in offspring of hypertensive parents. This may play a role in the pathogenesis of essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
130
2
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(148 citation statements)
references
References 28 publications
12
130
2
4
Order By: Relevance
“…Consistent with prior studies in humans and rats,2, 11, 12, 13, 14, 15, 16, 20, 21 flox mice exhibited a significant increase in plasma ET‐1 in response to CSS, whereas VEETKO mice exhibited no change in plasma ET‐1 following CSS. We found that pulmonary ET receptor expression and affinity are similar in VEETKO and flox mice, suggesting no differences in ET‐1 clearance capacity in VEETKO and flox mice.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with prior studies in humans and rats,2, 11, 12, 13, 14, 15, 16, 20, 21 flox mice exhibited a significant increase in plasma ET‐1 in response to CSS, whereas VEETKO mice exhibited no change in plasma ET‐1 following CSS. We found that pulmonary ET receptor expression and affinity are similar in VEETKO and flox mice, suggesting no differences in ET‐1 clearance capacity in VEETKO and flox mice.…”
Section: Discussionsupporting
confidence: 88%
“…Multiple studies in humans have observed an increase in plasma ET‐1 in response to laboratory‐induced stress,11, 12, 13, 14, 15, 16 and these findings have been further validated by a large clinical study of male and female participants 2. More important, prior studies have highlighted the importance of both a family history of CVD and preexisting CVD as modifiers of the stress responsiveness of plasma ET‐1, as reviewed by Yammine et al 8.…”
Section: Perspectivesmentioning
confidence: 99%
“…40 Although the precise mechanism involved in this failure is not clearly understood, an increased activation of sympathetic nervous system may be a mechanism contributing to the exaggerated exercise BP, and may probably have a key role in the pathogenesis of essential hypertension. 13,41,42 Previous studies have shown that normotensive men offspring of hypertensive parents show increased sympathetic nervous system activity in response to mental stress, 13 hand grip exercise 41 and GXT. 42 This study demonstrates that young normotensive women offspring of hypertensive parents also have increased resting, exercise and recovery NE, and exercise and recovery EPI than women with normotensive parents.…”
Section: Pwvmentioning
confidence: 99%
“…Higher exercise BP during a GTX has been associated with decreased endothelial vasodilator function in hypertensive men and women, 43 and several studies have shown that the basal release of endothelium-derived vasodilator nitric oxide is impaired in hypertensive subjects 44 and its normotensive offsprings. 45 Moreover, the levels of endothelium-derived vasoconstrictor ET-1 has shown to be increased in normotensive male offsprings of hypertensive parents during mental stress 13 and hand grip exercise. 41 In this study, we demonstrated for the first time an increase in ET-1 and decrease in NOx (metabolities of nitric oxide), during the basal, exercise and recovery phases of a GXT, in young normotensive women offspring of hypertensive parents, suggesting that the exaggerated exercise BP present in these women may be in part a function of an impaired endothelial vasodilator function.…”
Section: Pwvmentioning
confidence: 99%
See 1 more Smart Citation